2016
DOI: 10.1111/joes.12154
|View full text |Cite
|
Sign up to set email alerts
|

Management Control Systems in Family Firms: A Review of the Literature and Directions for the Future

Abstract: Family firms play a significant role in the global economy. Although family firm literature has devoted much time and effort to investigating topics concerning corporate governance, leadership, ownership and succession, accounting issues have received relatively scant attention. In this paper, we assemble and critically review extant literature on the choice of management controls. This is an essential topic for firms as management control systems (MCS) are used to make sure subordinates behave in function of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
78
2
35

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(119 citation statements)
references
References 121 publications
4
78
2
35
Order By: Relevance
“…Control mechanisms were found to reduce agency behavior by aligning individual and firm preferences, consequently resulting in higher financial performance (Chrisman et al 2007;Sieger et al 2013;Helsen et al 2016). We hypothesize in accordance with prior literature that the use of control mechanisms will avoid agency behavior by aligning individual and family (firm) preferences through specific monitoring and evaluation procedures (Sieger et al 2013;Eisenhardt 1989).…”
Section: Control Mechanisms and The Eo-performance Relationshipsupporting
confidence: 73%
See 3 more Smart Citations
“…Control mechanisms were found to reduce agency behavior by aligning individual and firm preferences, consequently resulting in higher financial performance (Chrisman et al 2007;Sieger et al 2013;Helsen et al 2016). We hypothesize in accordance with prior literature that the use of control mechanisms will avoid agency behavior by aligning individual and family (firm) preferences through specific monitoring and evaluation procedures (Sieger et al 2013;Eisenhardt 1989).…”
Section: Control Mechanisms and The Eo-performance Relationshipsupporting
confidence: 73%
“…Two promising context factors of entrepreneurial behavior in family firms are discussed in the following: management control mechanisms and family-related goals. Prior literature in management accounting already showed that family dynamics such as trust (Sundaramurthy 2008) lead to a reduction in information asymmetries (Senftlechner and Hiebl 2015) and therefore require more complex control and management initiatives (Helsen et al 2016). Our study demonstrates that in family firms the impact of particular EO dimensions on firm performance depends on the usage of control mechanisms and the adherence to family-related goals.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…Personnel control includes processes to involve, influence, motivate, and inspire, and it also considers personnel goals (Kleine and Weißenberger 2014). Nevertheless, such personnel goals develop not in isolation but through followup action controls (Kleine and Weißenberger 2014) during an operation rather than afterwards (Helsen et al 2016). Many of these are forward looking.…”
Section: Innovativeness In Personnel and Action Controlsmentioning
confidence: 99%